Proving Unlawful Discrimination in Capital Cases: In Quest of an Adequate Standard of Proof - Maučec, Gregor (Utrecht Journal of International and European Law, 2017)
In spite of some early judicial, political and scholarly discussions, as well as more recent scientific explorations of the topic, problems and concerns with proving discrimination in individual capital cases continue to be among the most debatable issues in human rights and criminal justice. In general, domestic courts (in particular US courts) seem to remain relatively perfunctory and hostile to individual discrimination challenges in capital trials. They normally require capital defendants alleging discrimination to prove something which is virtually impossible to prove. On the other hand, numerous capital defence attorneys, legal commentators and even some of the trial judges themselves lay strictures on the existing judicial approach which almost routinely rejects discrimination claims in capital cases. They contend that appropriate modifications in current legislative arrangements and mechanical adjudication policy and practice are urgent and indispensable for more equitable resolutions and for a truly even-handed criminal justice system. In particular, there are concerns regarding the adequate distribution of the burden of proof between the litigants. Moreover, no clear or uniform approach to this conundrum can be identified in the international jurisprudence. This article seeks to provide some definite answers to open and conceptual questions posed in an attempt to legally define ‘the minimum core content’ of the evidentiary standard – as implicitly contained in the relevant international human rights treaties’ provisions – to be applied in capital sentencing discrimination cases. Additionally, part of this same standard of proof can also qualify as a general principle of international law, particularly in relation to impartial, unbiased and non-discriminatory approaches and decision-making by the judges and jurors involved in complex capital cases.